REVIEWING THE “OASE” (ORGANIZATION OF AHLULBAYT FOR SOCIAL-SUPPORT AND EDUCATION); Its Creeds, Its Activities, and a Different Color within Indonesian Shi’is - Asep Nahrul Musadad (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The purpose of this paper is to discuss an Indonesian Shi’i movement called OASE (Organization of Ahlulbayt for Social-support and Education). Coordinated by Emilia Renita Az, OASE marks the unique movement of Shi’i women in Indonesia, along with the existing Shi’i representative organization in the country, such as IJABI (Ikatan Jama’ah Ahlul Bait Indonesia/The All-Indonesian Assembly of Ahlulbayt Associations) and ABI (Ahlul Bait Indonesia/Indonesian Ahlulbayt). Using the perspective of social-movement, this paper seeks to capture the origin of OASE, its basic creeds, and its contribution of social activities in the Indonesian public sphere. The three-fold layers (artifact, sociofact, and mentifact) are used to explore its social works. The researcher’s engagement with the leader of OASE in a depth-interview is the method to collect the data in addition to analyze several artifact including documents, photos, and posters. The research finds several important points, including the founding of OASE as the “child” of reformasi (post-new order Indonesia), the nature of shi’i philanthropic activities as their spirit of social works through the lens of the mentioned three-fold layers, and the position of OASE among the other Indonesian Shi’i groups in the light of the international context of shi’i marja’iyya